Pembelajaran berbasis google classroom bagi guru sekolah lanjutan - Muhiddin Palennari; Ismail Ismail; Abd. Muis (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Teachers in Enrekang are known to be very active in following the development of education, especially those relatedto teacher professional development. Several activities in the past five years have been included, including carrying out FocusGroup Discussion (FGD) which discusses the problems faced by teachers in the field, education and training activities,workshops, seminars, and a number of other scientific gatherings. These activities have a positive impact on improving teacherprofessional competence. However, in certain cases, they still experience a number of problems that demand to be resolvedimmediately, including learning based on information and communication technology, including learning based on Googleclassroom. Google classroom (GC) is known as one of the efficient and effective learning media in increasing student learningactivities and outcomes. Thanks to this, secondary school teachers in Enrekang Regency have not used it due to limitedknowledge and skills. To overcome the problems faced by partners, Google classroom-based learning design training wasconducted using workshops, discussion and question and answer methods, and independent assignments. The results of thisactivity can improve the ability of participants (secondary school teachers) in terms of applying Google classroom basedlearning.